Relationship of foot pain with the increased risk of falls in patients with Parkinson’s disease. - Jiménez-Cebrián, Ana María; Ruiz‐Sánchez, Francisco Javier; Losa-Iglesias, Marta Elena; Becerro-de-Bengoa-Vallejo, Ricardo; López López, Daniel; Montiel-Luque, Alonso; De Labra, Carmen; Saavedra‐García, Miguel Ángel; Navarro‐Flores, Emmanuel (Wiley, 2024)
Introduction Falls are one of the most frequent difficulties in patients with Parkinson's disease. The objective of this study was to determine the relationship between foot pain and the risk of falls in participants with Parkinson’s disease compared to a group of participants without Parkinson’s disease. Materials and Methods The subjects (124) were divided into two groups, cases (n = 62) and controls (n = 62). They completed the Downton scale that collects the following 5 dimensions: previous falls, medications, sensory deficit, mental state, and ambulation. Results Analyzing the Downton scale using dimensions, a significant difference was observed between both groups in all dimensions except mental state. Regarding the global result of risk of falls, the participants who had a diagnosis of Parkinson’s disease presented a high risk of falls, 40.3% compared to 3.2% of the non-Parkinson’s disease group, with statistically significant differences (p < 0.05). For the numerical value of the Downton scale, there was a clear statistically significant difference between groups (2.65 ± 0.96 vs. 1.31 ± 1.19). Conclusion This research confirms further evidence that people with Parkinson’s disease who suffer from foot pain are at high risk of falling, regardless of gender.
Keywords: Pies - Lesiones y heridas; Podología; Parkinson, Enfermedad de - Complicaciones y secuelas; Caídas; Enfermos de Parkinson; Downton fall risk index